IMPLEMENTATION OF SOCIAL AND ENVIRONMENTAL RESPONSIBILITY (TJSL) AT PT PLN (PERSERO) SULUTTENGGO DISTRIBUTION PARENT UNIT IN THE DIGITAL-BASED SMART HOME PROGRAM IN KAMPUNG BAHARI NUSANTARA DESA BUDO - Keren Irene Sengke; Wijaya Gautama; Paula Makal (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Corporate Social Responsibility (CSR) is a concept that refers to the company's responsibility to the environment and society to provide benefits both internally for the company and externally for the community and the government. The purpose of this article is to find out how PT PLN (Persero) Suluttenggo Main Distribution Unit manages the CSR program. This case study involves the people of Budo Village. The logical framework method through the development of tourist areas and the development of MSEs. The results of the study show that the natural aspect of this program helps in increasing the promotion of Mangrove Forest tourism in Budo Village. From the economic aspect, this program greatly supports the economy of the community and the government of Budo Village through the maintenance of tourist attractions and the improvement of MSEs with the existence of Smart Houses. From the social aspect, this program is expected to increase the productivity and living standards of the people of Budo Village. Children can learn and recreation at a leisurely pace without feeling overwhelmed. From the aspect of welfare, the first impact felt is the improvement of people's living standards, creating a smart community and always following technological developments. Second, the realization of the PLN Empowered Village Program